Approximate analytical methods for solving ordinary differential equations - Radhika, T. S. L. 1974-; Iyengar, T. K. V.; Rani, T. Raja 1972- (CRC Press, Taylor & Francis Group, 2015)
Approximate Analytical Methods for Solving Ordinary Differential Equations (ODEs) is the first book to present all of the available approximate methods for solving ODEs, eliminating the need to wade through multiple books and articles. It covers both well-established techniques and recently developed procedures, including the classical series solution method, diverse perturbation methods, pioneering asymptotic methods, and the latest homotopy methods.